Meeting the WHO physical activity guidelines and health-related quality of life of single parents in Ghana - Owusu-Sarpong, Obed Jones; Abass, Kabila; Osei-Tutu, Solomon; Hajek, André; Gyasi, Razak M. (Frontiers in Public Health, 2025)
PurposeImproving physical activity (PA) and health-related quality of life (HRQoL) is critically important for achieving the health-related sustainable development goal (SDG 3). However, data on the association between PA and HRQoL, particularly among single parents, are limited in low- and middle-income countries (LMICs). We examine the association between PA and HRQoL among single parents in Ghana and explore the modifying roles of sex, age, and spatial differences in this association.MethodsData on 627 single parents were obtained through a multi-stage stratified sampling technique. PA was assessed using the International Physical Activity Questionnaire-Short Form (IPAQ-SF). The EQ-5D-3L questionnaire was used to measure HRQoL. A hierarchical Ordinary Least Squares (OLS) regression models evaluated the hypothesized associations.ResultsPA was significantly associated with poor HRQoL even after accounting for all potential confounders (B = −0.298, SE = 0.132, p < 0.05). The association was further modified by sex (B = −0.619, SE = 0.206, p < 0.01) and age (B = −0.062, SE = 0.008, p < 0.001). Thus, the PA-HRQoL association was more pronounced among older and female single parents.ConclusionPhysical activity was negatively associated with poor HRQoL. Sex and age differences modified the association. Promoting PA may reduce poor HRQoL among single parents.